O parque e a estrada: conservação e desenvolvimento na história do Parque Estadual do Rio Doce (1944-1993 - Elisangela Maria Barbosa Santos (2019)
This work is an historical analysis of the management process of the Rio Doce State Park. During the research, it was possible to realize the importance of the road of Ponte Queimada bridge, located inside the Park, for the issues related to the object of study. Thus, it was taken as guiding principle the construction and maintenance of this Road and the tensions that were derived from the conflicts in relation to its use, which were considered an emblematic expression of the complex relationship between the actions toward the development and those toward the preservation, present between the 1940s and 1990s, in the history of Minas Gerais State and Brazil. The analysis of such tensions acted to examine, in a broader perspective, the political and environmental conflicts present in the Brazilian political scene during this period. At the end of the study, it was found that the contradictions and ambiguities within the entities responsible for the protection of nature, such as the Department of Agriculture, Trade, Industry and Labor and the State Forestry Institute, among other public institutions, were mainly responsible both to protect and to endanger the preservation of the Rio Doce State Park. This finding is the main contribution to other works related to the environmental policy, because it is believed that such problems have occurred in other public entities related to the environment.